The evaluation of 2568 patients with upper gastrointestinal bleeding - Ali ERGİN and Kadir AKSÖZ and Belkıs ÜNSAL and Günay ÖNDER and Zakir AKYOL and Uğur GÖNENÇ and Nafi YAZICIOĞLU and Belkıs ÜNSAL and Himmet KARACA and Sadun KOŞAY and et al. (Turkish Journal of Gastroenterology, 2020)
-